Internet of Things (IoT) Driven Water Management System for Efficient Level Control - Nzeanorue, Christian Chukwuemeka; Nnana, Ogba Samuel; Victoria, Shittu Sarah; Nzeanorue, Chibuike Godswill; Enabulele, Ewemade Cornelius; Olusola, Raphael Aduramimo; Jamiu, Ridwan Olamilekan; Daramola, Merinuibi Sunday; Stephen, Victor Ikechukwu; Ekunseitan, Kehinde Deji (Journal of Multidisciplinary Science: MIKAILALSYS, 2024)
Water is an essential and valuable resource in daily life, making its conservation crucial to prevent adverse effects. Storing water for domestic, industrial, agricultural, and other purposes is particularly important. Safe drinking water is increasingly becoming polluted due to the growing population and their demands for urbanization and industrialization. At the household level, some people leave electric water pumps running and either go to work or sleep, forgetting to turn off the pumps when the water container is full. This highlights the need for a reliable and continuous water supply. IoT plays a significant role in environmental monitoring, particularly in disaster management, early warning systems, and environmental data analytics. One major challenge in urban cities is water management, especially with the rapid growth of urbanization, necessitating sustainable urban development plans. To address these issues, we propose a "Water Level Monitoring System" solution. This paper presents an IoT-based water monitoring system for real-time applications. The system's sensors measure the water level in the tank, and the data is sent to a cloud server, allowing users to view it on a remote dashboard. This system can be used efficiently by both homeowners and industrial users, as well as other water utilities.